Quantifying the climate impact of emissions from land-based transport in Germany. (December 2018) - Hendricks, Johannes; Righi, Mattia; Dahlmann, Katrin; Gottschaldt, Klaus-Dirk; Grewe, Volker; Ponater, Michael; Sausen, Robert; Heinrichs, Dirk; Winkler, Christian; Wolfermann, Axel; Kampffmeyer, Tatjana; Friedrich, Rainer; et al.
Highlights: A method to quantify the climate effects of regional land-based transport emissions is presented. The method is applied to the output of transport and emission models for Germany. The results reveal that transport emissions in Germany contribute to global warming by 0.01 K. The approach enables the evaluation of strategies to reduce the climate impact of transportation. Abstract: Although climate change is a global problem, specific mitigation measures are frequently applied on regional or national scales only. This is the case in particular for measures to reduce the emissions of land-based transport, which is largely characterized by regional or national systems with independent infrastructure, organization, and regulation. The climate perturbations caused by regional transport emissions are small compared to those resulting from global emissions. Consequently, they can be smaller than the detection limits in global three-dimensional chemistry-climate model simulations, hampering the evaluation of the climate benefit of mitigation strategies. Hence, we developed a new approach to solve this problem. The approach is based on a combination of a detailed three-dimensional global chemistry-climate model system, aerosol-climate response functions, and a zero-dimensional climate response model. For demonstration purposes, the approach was applied to results from a transport and emission modeling suite, which was designed to quantify the present-day and possible future transport activities in Germany and the resulting emissions. The results show that, in a baseline scenario, German transport emissions result in an increase in global mean surface temperature of the order of 0.01 K during the 21st century. This effect is dominated by the CO2 emissions, in contrast to the impact of global transport emissions, where non-CO2 species make a larger relative contribution to transport-induced climate change than in the case of German emissions. Our new approach is ready for operational use to evaluate the climate benefit of mitigation strategies to reduce the impact of transport emissions.